(untitled) (Latakia University Journal -Biological Sciences Series, 2023)
The experiment was carried out during the agricultural seasons 2021/2023 in a nursery at the Faculty of Agricultural engineering. Tishreen University- Lattakia- Syria. by the cultivation of three Tobacco genotypes Prilep- Basma- Shak Elbent. Half diallel cross was made between different genotypes of tobacco. In The following season, an evaluation of the genotypes was performed. that were distributed according to the Randomized Complete Block Design (RCBD) with three replicates per treatment. To estimate the heterosis, general and specific combining ability, nature of gene action for: Fresh Weight of Leaves, Dry Weight of Leaves, DWL / FWL, Weight Leaf Specific. The results show high differ significantly for all traits, which refer to differ among the parents. The genetic analysis show important both additive and dominant effects to heredity all characters studies. The variance ratio of GCA to SCA was more than one (1) for all traits. The (Shak Elbent) parents show high GCA for (Fresh Weight of Leaves, Dry Weight of Leaves, DWL / FWL, Weight Leaf Specific), the hybrid (Prilep × Shak Elbent) show the highest SCA of Weight Leaf Specific. The highest values for heterosis in this study it was for the Weight Leaf Specific to the cross (Prilep × Shak Elbent) which it (16.418)%.